Sound Wave Absorption Coefficient and Sound Velocity in Thermally Modified Wood - Przemysław Mania; Artur Flach; Marta Pilarska (Applied Sciences, 2023)
The present work analyses the absorption coefficient of sound waves and the speed of sound propagation in thermally modified wood. The high resistance to weathering, fungi, and better dimensional stability, and therefore the broad physical properties of this material, are well known. However, the literature lacks numerous analyses of its acoustic characteristics. During the study, high-density species, such as oak, red oak, and beech were used, in contrast to pine. Pine wood during this test was characterised by a most rapid increase in the sound absorption coefficient value, in the range of 1000–6300 Hz, and reached the highest value from all wood species. Among all species, the highest value of the examined parameter was obtained for beech wood and pine wood, which were 0.213 (at frequency 3 kHz) and 0.183 (at 6.3 kHz), respectively. The sound velocity decreased for all species only in the tangential direction.